Detecting Jump Activities on Ultra-High Frequency VIX: Pricing VIX Futures and Market Timing Hedge Funds - GOH, Choo Yong, Jeremy (Institutional Knowledge at Singapore Management University, 2012)
The study indicates that Brownian motion, finite and infinite activity jumps are present in the ultra-high frequency VIX data, especially when taking into account the impact of market microstructure noise on various statistics. The total quadratic variation can be split into a continuous component of 29% and a jump component of 71%. Modeling finite-activity jumps is found important for pricing front-month VIX futures. But for simple trading strategies, incorporating infinite-activity jumps yields the best performance with an average absolute error of one-and-a-half to two volatility points each day. In addition, hedge funds deliver out-of-sample performance respective of jump activities on ultra-high frequency VIX. In particular, strategies exposing to long “volatility” and “market event risk” that follow large jumps on VIX tend to deliver positive performance in extreme market environments, while short “volatility” funds perform best in calm markets that follow Brownian motion.